Design of Transboundary Observation System for Plant Protection UAV Based on Improved Winding Number Method and Android. Issue 17 (2018) - Hao, Ziyuan; Yang, Wei; Li, Minzan; Chen, Yuqing; Zhu, Licheng; Sun, Hong
Abstract: In order to monitor the work trajectory of the plant protection unmanned aerial vehicle (UAV) in real time, and judge whether there is a transboundary behavior during the spraying work of the plant protection UAV, transboundary observation system for plant protection UAV was designed. A new algorithm that called Improved Winding Number method was proposed to judge the relative ubiety between real-time trajectory point and work boundary of UAV in this system, which was used to transform the problem of two-dimensional (2D) plane into three-dimensional (3D) space on the basis of the Winding Number method. Then the computation part of this algorithm was optimized, which simplified the coordinate relation between the trajectory point and work boundary. On the basis of this algorithm, client software of transboundary observation system for plant protection UAV based on Android was designed, which combined the Baidu Eagle Eye SDK and made full use of the advantages of the Android mobile terminal. Finally, the function of trajectory tracing for the plant protection UAV and transboundary alarm was realized in this system. By testing the performance of transboundary observation system, it showed that this system had high accuracy and stability.